Ответ:
Пошаговое объяснение:
а). 1,2m^2/√1,2m^2=1,2m^2*√1,2m^2/√1,2m^2*√1,2m^2=
1,2m^2*√1,2m^2/1,2m^2=√1,2m^2
б). 36/√(-0,6)^2*x=36*√x/(-0,6)*√x*√x=36√x/(-0,6)*x= -60√x/x
в). 2*(2+√3)/(2-√3)*(2+√3)=2*(2+√3)/(4-3)=4+2√3
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Пошаговое объяснение:
а). 1,2m^2/√1,2m^2=1,2m^2*√1,2m^2/√1,2m^2*√1,2m^2=
1,2m^2*√1,2m^2/1,2m^2=√1,2m^2
б). 36/√(-0,6)^2*x=36*√x/(-0,6)*√x*√x=36√x/(-0,6)*x= -60√x/x
в). 2*(2+√3)/(2-√3)*(2+√3)=2*(2+√3)/(4-3)=4+2√3